Water Quality Assessment for Irrigation Water Use in Lake Hazar Basin, Elazığ, Turkey - Çeliker, Murat; Parlakyıldız, Nurettin; Öztürk, Mualla (My University, 2020)
The goal of this work was to research the suitability of water sources for agricultural use in the Lake HazarBasin For this purpose, samples are taken from 61 locations during the wet period and 60 locations during the dryperiod in 2015 and analyzed pH, electrical conductivity, calcium, magnesium, sodium, potassium, bicarbonate,chloride and sulfate parameters. Based on these analyses sodium percentage (Na%), sodium absorption ratio (SAR),residual sodium carbonate (RSC), magnesium ratio (MR), permeability index (PI) and Kelly’s ratio (KR) werecalculated. Also, the usability of groundwater in agricultural activities is evaluated according to Wilcox and UnitedStates Salinity Laboratory (USSL) Diagrams. The EC, SAR, Na%, RSC, PI, KR and MR values revealed that suitability ofwaters as irrigation water, except for a few locations close to the lake. Similar results were obtained fromclassifications made according to USLL and Wilcox diagrams. The thematic maps of water quality parametersdisplayed that the groundwater quality decreases along the flow path from high elevations to lake level.
Keywords: Su Kaynakları